Perampanel Affects Up-Stream Regulatory Signaling Pathways of GluA1 Phosphorylation in Normal and Epileptic Rats - Kim, Ji-Eun; Choi, Hui-Chul; Song, Hong-Ki; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2019)
To elucidate the pharmacological properties of perampanel [2-(2-oxo-1-phenyl-5-pyridin-2-yl-1,2-dihydropyridin-3-yl)benzonitrile, a novel noncompetitive antagonist of AMPA receptor], we investigated its effects on the up-stream regulatory pathways of GluA1 phosphorylation including protein kinase C (PKC), Ca2+-calmodulin-dependent protein kinase II (CAMKII), protein kinase A (PKA), extracellular signal-regulated kinase 1/2 (ERK1/2), c-Jun N-terminal kinase (JNK), protein phosphatase (PP) 1, PP2A and PP2B in normal and pilocarpine-induced epileptic rat model using Western blot analysis. In normal animals, perampanel affected GluA1 expression/phosphorylation, PKC, CAMKII, PKA, ERK1/2, JNK and PPs activities. In epileptic rats, perampanel effectively inhibited spontaneous seizure activities. Perampanel enhanced phospho (p)-GluA1-S831 and -S845 ratios (phosphoprotein/total protein), while it reduced GluA1 expression. Perampenal also increased pCAMKII and pPKA ratios, which phosphorylate GluA1-S831 and -S845 site, respectively. Perampanel elevated pJNK and pPP2B ratios, which phosphorylates and dephosphorylates both GluA1-S831 and -S845 sits. Perampanel also increased pERK1/2 ratio in epileptic animals, while U0126 (an ERK1/2 inhibitor) did not affect pGluA1 ratios. Perampanel did not influence PKC, PP1 and PP2A expression levels and their phosphorylation ratios. In addition, perampanel did not have a detrimental impact on cognitive abilities of epileptic and normal rats in Morris water maze test. These findings suggest that perampanel may regulate AMPA receptor functionality via not only blockade of AMPA receptor but also the regulations of multiple molecules (CAMKII, PKA, JNK and pPP2B)-mediated GluA1 phosphorylations without negative effects on cognition, although the effects of perampanel on PKC, PP1 and PP2A activities were different between normal and epileptic rats.